A NOVEL LC-MS/MS TECHNIQUE FOR THE QUANTITATION OF LURBINECTEDIN IN HUMAN PLASMA: APPLICATION OF STABILITY STUDIES - KOTHA, PRATHYUSHA; BARU, CHANDRASHEKARA RAO; KANTLAM, CHAMAKURI (International Journal of Applied Pharmaceutics, 2025)
Objective: A linear and precise liquid chromatography coupled with tandem mass spectrometry method was developed and validated for the quantification of lurbinectedin in plasma. Canagliflozin served as an internal standard (IS). Methods: The plasma extraction utilized 5 ml of ethyl acetate as the solvent. The examination was performed utilizing a Zorbax ODS (50 mm × 2.1 mm x 3µ) stationary phase at ambient conditions, with a mobile phase comprising 0.1% HCOOH, acetonitrile, and methyl alcohol in a ratio of 15:50:35. The measurement of the mobile phase’s flow rate was recorded at 0.4 ml/min. In positive ionization mode utilizing electrospray, the drug and internal standard were detected, resulting in mass transitions of (m/z): Lurbinectedin, 785.30/711.20 and Canagliflozin (IS), 445.15/267.12. Results: A linear correlation was established between the concentrations of Lurbinectedin and their corresponding peak proportions to canagliflozin across the concentration range of 0.2-3200 ng/ml. The precision for Lurbinectedin, measured both within the same day and across different days, was determined to be ≤5.18%. Inter and intra-day bias ranged from −4.17% to 4.53. The measured average extraction recovery for Lurbinectedin was found to be 99.23%. The measurement of the internal standard’s recovery was found to be 98.31%. Lurbinectedin was subjected to thorough assessment regarding its long-term, freeze-thaw, bench top, short-term stability, auto sampler, dry extract, and stock solution stability at both low quality control (QC) and high QC levels, showing consistent stability across all evaluated conditions. Conclusion: The developed method has become a cornerstone of modern clinical laboratories due to its versatility, sensitivity, and precision, and its ability to support both routine clinical diagnostics and cutting-edge personalized medicine.